Identifica????o e adapta????o das melhores pr??ticas de gerenciamento de projetos para atua????o com projetos de inova????o social na ??rea da sa??de - Carvalho, Marcos Sim??es de (2017)
The objective of this study was to identify and adapt the best practices of project management to be applied in projects of social innovation in the healthcare area. The work that is characterized as an exploratory qualitative research, using in-depth interviews and confirmatory focus group as data collection techniques, consisted of searching the literature on sustainable development, social sustainability, social innovation and project management, for approaches through which the authors point out to gaps in the adoption of administrative and project management routines that increase the potential for success of activities related to social innovation. The results showed how the main factors that motivate the emergence of social innovation can be better managed based on the development of specific competence elements, consideration of the organizational elements, as well as the management of the procedural and operational elements, making the projects to adequately meet stakeholders' interests and expectations. The organization of the factors related to the management of social innovation projects in the healthcare area also resulted in the construction of a framework developed with the proposal of serving as an instrument for professionals working in this area. It is suggested, however, that future studies be done in other areas with high demand for services to be provided to the population, as well as investigate a greater number of cases using quantitative research methods. Considering that most of the literature on social innovation, to date, presents more considerations on the conceptual aspects of this construct, the present study brings as main contribution the possibility of research on the practical questions regarding the planning and execution of social innovation projects, whereas from the theoretical point of view the study contributes with a new approach that relates the discipline of project management with the phenomenon of social innovation, however, without intending as a work that exhausts the subject. The presentation of the framework as a practical tool for the management of social innovation projects is configured as a differential of the study, in addition to having been used as methodological procedure the accomplishment of a confirmatory focus group with professionals experienced in social projects as a way of validating the proposal of the model.